Best Participatory Practices in Mangrove Conservation Management: The Case in the Mangrove Rehabilitation Program in the Fishing Villages in the Philippines - Tomaquin, Ramel D. (Journal of Asian Multicultural Research for Social Sciences Study, 2023)
The mangrove conservation program is one of the measures to address climate change at the village or community level and is the most effective and sustainable. For it entails a community participatory approach and is anchored on the participation of the private sector, and people’s organizations. Bayabas, a coastal municipality of Surigao del Sur, in the Philippines with the communities Cabugo, Magobawok, Belete, and La Paz, the sites of the study, has a robust mangrove conservation program. The study used mixed methods of survey, ethnographic, and observation/case study methods which capture the organizational culture of the sites. The findings of the study include the following: The Mangrove Conservation sites were established in response to the significant provisions of the Local Government Code of 1991 bearing on Environmental Conservation duly supported by an Ordinance of the LGU of Bayabas. The operation of the Mangrove Conservation sites was being assisted by the People’s Organization (PO) which is also a quasi-cooperative for fishers. The POs were established by a joint effort of the PFAR/BFAR and the LGU of Bayabas. Sagip Wakatan, the Mangrove Conservation Program of the LGU of Bayabas was anchored on food security, sustainable development, people’s empowerment, eco-tourism, and the response to climate change initiatives at the grassroots levels. Livelihood integration is one of the most important features of the Mangrove Conservation Program and was directly channeled into the four (4) People’s Organizations (POs). The fishers across four (4) sites are active enough in their participation in the Mangrove Conservation.